2015
DOI: 10.1200/jco.2014.56.5119
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, Randomized, Double-Blind, Multicenter Trial Comparing Orteronel (TAK-700) Plus Prednisone With Placebo Plus Prednisone in Patients With Metastatic Castration-Resistant Prostate Cancer That Has Progressed During or After Docetaxel-Based Therapy: ELM-PC 5

Abstract: Purpose Orteronel (TAK-700) is an investigational, nonsteroidal, reversible, selective 17,20-lyase inhibitor. This study examined orteronel in patients with metastatic castration-resistant prostate cancer that progressed after docetaxel therapy. Patients and Methods In our study, 1,099 men were randomly assigned in a 2:1 schedule to receive orteronel 400 mg plus prednisone 5 mg twice daily or placebo plus prednisone 5 mg twice daily, stratified by region (Europe, North America [NA], and non-Europe/NA) and Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 25 publications
2
69
2
5
Order By: Relevance
“…A recent analysis of the phase III COU-AA-302 (Abiraterone Acetate in Asymptomatic or Mildly Symptomatic Patients With Metastatic Castration-Resistant Prostate Cancer) trial demonstrated a significant correlation between rPFS and OS. 22 However, the lack of correlation between rPFS and OS in this study and in other phase III studies in mCRPC [24][25][26] illustrates that significant improvements in rPFS may not always translate into longer-term survival benefit.…”
Section: Discussioncontrasting
confidence: 42%
“…A recent analysis of the phase III COU-AA-302 (Abiraterone Acetate in Asymptomatic or Mildly Symptomatic Patients With Metastatic Castration-Resistant Prostate Cancer) trial demonstrated a significant correlation between rPFS and OS. 22 However, the lack of correlation between rPFS and OS in this study and in other phase III studies in mCRPC [24][25][26] illustrates that significant improvements in rPFS may not always translate into longer-term survival benefit.…”
Section: Discussioncontrasting
confidence: 42%
“…In contrast to the other CYP17 inhibitors tested, orteronel had no activity on the WT or mutant AR. In recent phase III studies of CRPC, ELM-PC 4 (chemotherapy-naive) and ELM-PC 5 (progression on docetaxel), orteronel did not meet the primary overall survival endpoints (58,59). The authors speculate that this resulted from patient crossover in Europe and North America to abiraterone and enzalutamide, which had been recently approved and were widely available in these areas.…”
Section: Methodsmentioning
confidence: 98%
“…It follows that inhibiting the spread of cells through the circulation would represent a therapeutic objective that is clinically meaningful. 8,[10][11][12][13][14] After the demonstration of CTC conversion rates between 35% and 40% in three phase II studies of abiraterone and enzalutamide, [15][16][17] a collaboration was initiated with the US FDA Center for Diseases and Radiologic Health to study post-treatment CTCcontaining end points as potential surrogates for survival. To do so, the CTC biomarker question was embedded in a series of phase III registration trials with a primary end point of overall survival.…”
mentioning
confidence: 99%